Relationship between preterm, low birth weight, and development defects of enamel in the primary dentition: A meta-analysis - Xu, Shan; Zhao, Caiyun; Jia, Liying; Ma, Zhe; Zhang, Xiaolin; Shi, Hong (Frontiers in Pediatrics, 2022)
Background This study aimed to systematically analyze the relationship between preterm (PT), low birth weight (LBW), and developmental defects of enamel (DDE) in the primary dentition. Methods Following the retrieval of the databases, case–control studies, cross-sectional studies, and cohort studies on the relationship between PT, LBW and DDE, which had been published in English or Chinese up to January 2022 were included. The data about odds ratio (OR) and 95% confidence interval (95% CI) were extracted and calculated using STATA 12.0 Software. Case–control studies were evaluated using the Newcastle–Ottawa Scale (NOS), while cross-sectional studies and cohort studies were evaluated using the JBI scale. The heterogeneity of each study was evaluated using the Q test. Results A total of 15 studies were included, of which 8 studied the relationship between PT and DDE, and 13 explored the relationship between LBW and DDE including three about the relationship between very low birth weight (VLBW) and DDE. Seven studies explored the relationship between PT, LBW, and DDE. The results of this meta-analysis showed that both PT and LBW especially VLBW (OR = 7.19, 95% CI: 4.98–10.38) were risk factors for DDE in the primary dentition (OR = 2.33, 95% CI: 1.55–3.51) (OR = 1.67, 95% CI: 1.08–2.59). The subgroup results showed that PT and LBW were both associated with the occurrence of enamel hypoplasia (EHP) (OR = 6.89, 95% CI: 3.33–14.34; OR = 2.78, 95% CI: 2.10–3.68) rather than enamel opacity (OR = 0.94, 95% CI: 0.55–1.61; OR = 1.03, 95% CI: 0.66–1.61). There was no publication bias about the included studies (P = 0.75 > 0.05; P = 0.47 > 0.05). Conclusion This meta-analysis demonstrated that both PT and LBW especially VLBW are associated with a higher risk of DDE in the primary dentition. PT and LBW are both related to the occurrence of EHP. However, the relationship between PT, LBW, and enamel opacity has not been verified. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?, identifier: CRD42021262761.